Assessment and Optimization of 2T Perovskite/CIGS Tandems via Data-Driven and Optoelectronic Modelling - Giliberti, Gemma; Farias‑Basulto, Guillermo; Jäger, Klaus; Mehlhop, Thede; Kaufmann, Christian A.; Carlo, Aldo Di (Nano-Micro Letters, 2026)
The global transition to a fossil-free energy system highlights the need for photovoltaic technologies that combine high efficiency with scalability, durability, and flexibility. Monolithic perovskite/Cu(In,Ga)Se2 tandem solar cells (TSCs) are an attractive thin-film alternative to perovskite/silicon TSCs, combining low-temperature processing, mechanical flexibility, and radiation tolerance. However, their practical potential remains constrained by coupled optical, electronic, and interfacial losses. This work develops a modelling approach integrating calibrated optical simulations, drift–diffusion device modelling, and a Shockley–Queisser (SQ) formalism, which incorporates empirical non-radiative recombination factors extracted from an external database. Starting from a certified 24.6% Helmholtz-Zentrum Berlin für Materialien und Energie GmbH TSC, the analysis identifies the dominant bottlenecks, quantifies the impact of defect passivation, optical optimization, and bandgap tuning, and extends the assessment to annual energy yield across representative climates. The results estimate practical efficiency limits above 35% and demonstrate significant energy-yield gains under real outdoor conditions, compared with perovskite and Cu(In, Ga)Se2 stand-alone devices, for both fixed-tilt and one-axis tracking configurations. At the same time, the database-informed SQ formalism provides a realistic benchmark by linking empirical non-radiative recombination factors to device performance, supporting consistent assessment across tandem architectures. Overall, these findings position perovskite/CIGS tandems as credible high-performance candidates within the landscape of next-generation photovoltaic technologies. Highlights: 1 Combined experimental characterization and physics-based modelling of the certified 24.6% perovskite/CIGS tandem reveal CdS/CIGS interfacial recombination and perovskite bulk defects induced by surface roughness. 2 Stepwise optimization integrating calibrated simulations with a data-driven Shockley–Queisser analysis demonstrates an efficiency potential exceeding 35% through targeted defect passivation and optical refinements. 3 Controlled bandgap tuning further enhances both the achievable efficiency and annual energy yield, provided the material quality is preserved across the full device stack.